2x+-1-6=10+-10x+6

Simple and best practice solution for 2x+-1-6=10+-10x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+-1-6=10+-10x+6 equation:


Simplifying
2x + -1 + -6 = 10 + -10x + 6

Reorder the terms:
-1 + -6 + 2x = 10 + -10x + 6

Combine like terms: -1 + -6 = -7
-7 + 2x = 10 + -10x + 6

Reorder the terms:
-7 + 2x = 10 + 6 + -10x

Combine like terms: 10 + 6 = 16
-7 + 2x = 16 + -10x

Solving
-7 + 2x = 16 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
-7 + 2x + 10x = 16 + -10x + 10x

Combine like terms: 2x + 10x = 12x
-7 + 12x = 16 + -10x + 10x

Combine like terms: -10x + 10x = 0
-7 + 12x = 16 + 0
-7 + 12x = 16

Add '7' to each side of the equation.
-7 + 7 + 12x = 16 + 7

Combine like terms: -7 + 7 = 0
0 + 12x = 16 + 7
12x = 16 + 7

Combine like terms: 16 + 7 = 23
12x = 23

Divide each side by '12'.
x = 1.916666667

Simplifying
x = 1.916666667

See similar equations:

| 12d+5e-7d= | | 1=4.5-2p+2.333333p | | 5k(k-2)-8k=-34 | | 1+x-6x=11 | | 5x=2x+42 | | 4p+8p-p= | | -7y=9-10y | | -5t-4=2t+14 | | 5x+1y=112 | | 1.25x=15.25 | | 6w+12=48 | | (5x-2)(3x+4)=(3x-5)(5x+1)+15 | | 4x+152=6x+166 | | 4k^2+3k-7=0 | | 9p+5q-2p= | | X-3+8=20 | | 3p+9=6p | | 5x-4+3=19 | | 5b-12b-90= | | 4k^2+11k+7=0 | | -7-3k=-4k | | 7j+4j+7k= | | -4t-7t= | | 360=x+7+2x-1 | | 4x+8=9x-7 | | 1/7-t/7=-5/7 | | -2(18-3x)=7y+2y | | 180=x+5+x+6+x+7 | | 9-6*x=-15 | | 18p=8 | | 75(2x-3)-1=5 | | 5g+6=51 |

Equations solver categories